2021
DOI: 10.3390/foods10051129
|View full text |Cite
|
Sign up to set email alerts
|

Mild Pretreatments to Increase Fructose Consumption in Saccharomyces cerevisiae Wine Yeast Strains

Abstract: The present research investigates the effect of different pretreatments on glucose and fructose consumption and ethanol production by four Saccharomyces cerevisiae wine strains, three isolated and identified from different wine regions in Turkey and one reference strain. A mild stress temperature (45 °C, 1 h) and the presence of ethanol (14% v/v) were selected as pretreatments applied to cell cultures prior to the fermentation step in synthetic must. The goodness fit of the mathematical models was estimated: l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Ethanol production correlated with AUC, μmax, and fructose consumption, but not with consumed glucose. This might seem strange, but [55] reported that their statistical data analysis evidenced that an increase in or change to the amount of consumed glucose or fructose did not cause the same increase in or change to the amount of produced ethanol. On day 7, the significant correlations were the same as on day 3, except for ethanol production, which did not correlate with the other parameters (Supplementary Table S2).…”
Section: Correlation Analysismentioning
confidence: 98%
“…Ethanol production correlated with AUC, μmax, and fructose consumption, but not with consumed glucose. This might seem strange, but [55] reported that their statistical data analysis evidenced that an increase in or change to the amount of consumed glucose or fructose did not cause the same increase in or change to the amount of produced ethanol. On day 7, the significant correlations were the same as on day 3, except for ethanol production, which did not correlate with the other parameters (Supplementary Table S2).…”
Section: Correlation Analysismentioning
confidence: 98%
“…Ethanol production correlated with AUC, µ max and fructose consumption, but not with glucose consumption. This may seem strange, but Karaoglan et al [57] reported that their statistical data analysis showed that increasing or changing the amount of glucose or fructose consumed did not result in the same increase in the amount of ethanol produced. On day 7, the significant correlations were the same as on day 3, except for ethanol production, which did not correlate with the other parameters (Supplementary Table S2).…”
Section: Correlation Analysismentioning
confidence: 99%
“…[5][6][7] In this process, yeast will convert sucrose into glucose, fructose and other monosaccharides by invertase, among which glucose is preferentially used by the yeast. 8,9 In the baking industry, the glucose content of sweet doughs usually ranges from 5% to 20%, even up to 30%. 6,10 In the process of using yeast to produce these products, yeast is susceptible to high-sugar stress.…”
Section: Introductionmentioning
confidence: 99%
“…When making bread, bakers usually choose to add exogenous cane sugar to the sourdough to become a sweet dough with a rich sweetness and use the dough to make bread after it has been fermented for a day or more 5‐7 . In this process, yeast will convert sucrose into glucose, fructose and other monosaccharides by invertase, among which glucose is preferentially used by the yeast 8,9 . In the baking industry, the glucose content of sweet doughs usually ranges from 5% to 20%, even up to 30% 6,10 .…”
Section: Introductionmentioning
confidence: 99%